Therapeutic agents for machine perfusion of donor organs - O. N. Rzhevskaya; V. M. Magilevets; R. S. Islamgazin; B. I. Yaremin; E. Yu. Anosova; A. G. Balkarov; M. S. Novruzbekov (Трансплантология (Москва))
Background. The urgency of the unmet need for transplant care dictates the necessity to use organs from suboptimal donors. Machine perfusion, which is actively developing at the present time, is designated to solve this problem. The literature presents novel technologies of ex vivo and in vivo machine perfusion of donor organs, which make it possible to improve their functions and perform a successful transplant. The most promising areas of research both in animals and in humans may be identified by reviewing the literature sources on this subject.The aim was to analyze the world experience of using therapeutic agents in machine perfusion of donor organsMaterial and methods: sources from 2015 to 2023 found in PubMed, Google Scholar, eLibrary databasesConclusion. The rapid progress in lung, liver and kidney transplantation has made it possible to use grafts from asystolic donors for patients in urgent need of donor organs. In turn, these advances have also prompted the study of potential therapeutic agents that can be used during perfusion.